RISK BASED INTERNAL AUDITING (RBIA) : SUATU PENDEKATAN DALAM AUDIT INTERNAL - Felisia . (Bina Ekonomi, 2010)
Internal auditing has evolved from accounting oriented to management oriented. The past role of internal auditor as the 'watchdog’ now has evolved into internal consultant, which gives input for organization's improvement, and also as a catalyst for the organization. The scope of auditing has become broader, not only focusing on financial audit and compliance audit, but also on risk management, and on every aspect that influenced organizations' performance. The audit orientation now has moved toward auditing based on risks. By applying risk based internal auditing, internal auditors are expected to improve their efficiency and effectiveness in doing audit. In designing Risk Based Internal Auditing (RBIA), internal auditors are expected to cooperate with the organization's committee, in order to obtain clear understanding about the expectation of auditing and monitoring, and how these activities can be grouped to minimalize risks in the organization. Risks triggered RBIA, and the function of RBIA is to report whether those risks have been controlled. Key Words : internal auditing, Risk Based Internal Auditing, inherent risk, residual risk, risk appetite